2005
DOI: 10.1039/b508500d
|View full text |Cite
|
Sign up to set email alerts
|

Selective detection of minor prototropic tautomers in low-symmetry tetraazaporphyrin derivatives by the combined use of electronic absorption, MCD, and CI calculations

Abstract: A series of low-symmetry metal-free tetraazaporphyrin (TAP) derivatives, i.e. monobenzo-substituted (1H2), adjacently dibenzo-substituted (2AdH2), oppositely dibenzo-substituted (2OpH2), and tribenzo-substituted (3H2) TAP derivatives, has been investigated by the combined use of electronic absorption, MCD, and CI calculations, proving the existence of two prototropic tautomers in 1H2 and 3H2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…The absorption spectra of the metal‐free Pzs 5a – c show a strong UV Soret transition at 333 nm with two shoulders at around 315 and 372 nm and two broad Q x ‐ and Q y ‐band transitions at around 647 and 710 nm, respectively, and a broad band of lesser intensity centered at 494 nm, which can be assigned to the S(n)→π* transition 17. The absorption spectra of compounds 5a – c are very similar to those reported for other low‐symmetry metal‐free Pzs in which two pyrrole protons should be bonded to the pyrrole ring in the x axial direction 18. Interestingly, the absorption spectra of 4c , with eight long alkyl chains, in a mixed solution of CH 2 Cl 2 /MeOH (0 → 40 % MeOH, v/v) reveal that 4c can be induced to form aggregates, as shown by a decrease and broadening of the band at 745 nm and an increase and blueshifting of the band at 678 nm (Q band at 678 nm → 673 nm; Figure 2, b) 1j…”
Section: Resultssupporting
confidence: 64%
“…The absorption spectra of the metal‐free Pzs 5a – c show a strong UV Soret transition at 333 nm with two shoulders at around 315 and 372 nm and two broad Q x ‐ and Q y ‐band transitions at around 647 and 710 nm, respectively, and a broad band of lesser intensity centered at 494 nm, which can be assigned to the S(n)→π* transition 17. The absorption spectra of compounds 5a – c are very similar to those reported for other low‐symmetry metal‐free Pzs in which two pyrrole protons should be bonded to the pyrrole ring in the x axial direction 18. Interestingly, the absorption spectra of 4c , with eight long alkyl chains, in a mixed solution of CH 2 Cl 2 /MeOH (0 → 40 % MeOH, v/v) reveal that 4c can be induced to form aggregates, as shown by a decrease and broadening of the band at 745 nm and an increase and blueshifting of the band at 678 nm (Q band at 678 nm → 673 nm; Figure 2, b) 1j…”
Section: Resultssupporting
confidence: 64%
“…However, in the case of the hydroporphyrin free-base compounds, the possibility of different tautomers exists and needed to be addressed (Figure ). In all the calculations, we found that the “ac” NH tautomers are at least ∼28 kcal/mol less stable than the corresponding NH tautomers. Thus, only the “bd” tautomers were considered.…”
Section: Resultsmentioning
confidence: 79%
“…22 As shown in Fig. 12, the systematic introduction of fused benzo-rings in metal-free TAPs results in "prototropic" tautomerism between X and Y, which is created by the difference in the positions of the two pyrrole protons with respect to the benzo-rings.…”
Section: Evaluations Of Prototropic Tautomers Of Low Symmetry Tapmentioning
confidence: 98%
“…A number of MCD studies on the effect of lowering the symmetry of metal-free TAPs have been carried out not only to clarify the degeneracy of the excited singlet states in these compounds but also to detect the tautomers generated by the positioning of the two pyrrole protons around the N4 ring. 22 As shown in Fig. 12, the systematic introduction of fused benzo-rings in metal-free TAPs results in "prototropic" tautomerism between X and Y, which is created by the difference in the positions of the two pyrrole protons with respect to the benzo-rings.…”
Section: Evaluations Of Prototropic Tautomers Of Low Symmetry Tap Der...mentioning
confidence: 99%